2021
DOI: 10.1002/alr.22912
|View full text |Cite
|
Sign up to set email alerts
|

Rhinology Medicare reimbursements have not been keeping up with inflation

Abstract: Background Studies have suggested that physicians are steadily being paid less per Medicare service over time based on inflation‐adjusted dollars. The objective of this study was to determine whether this phenomenon was true for rhinologic procedures. Methods This study was a retrospective analysis of the 2000‐2021 Centers for Medicare & Medicaid Services (CMS) Physician Fee Schedule investigating fees for in‐office endoscopies (Current Procedural Terminology [CPT] codes 31231‐31238), in‐office balloon ostial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…This decrease is consistent with other studies on Medicare reimbursement both within the field of otolaryngology 23 and otology 24 as well as at large in fields such as general surgery, 25 neurosurgery, 26 orthopedics, 27 and plastic surgery 28 . Inflation‐adjusted Medicare compensation per rhinologic procedure decreased significantly with an average total percent decrease of 36.09% for high relative value unit (RVU) procedures 29 . In the other specialties, the average nominal dollar reimbursements have increased or decreased by less than 10% 25–28 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This decrease is consistent with other studies on Medicare reimbursement both within the field of otolaryngology 23 and otology 24 as well as at large in fields such as general surgery, 25 neurosurgery, 26 orthopedics, 27 and plastic surgery 28 . Inflation‐adjusted Medicare compensation per rhinologic procedure decreased significantly with an average total percent decrease of 36.09% for high relative value unit (RVU) procedures 29 . In the other specialties, the average nominal dollar reimbursements have increased or decreased by less than 10% 25–28 .…”
Section: Discussionsupporting
confidence: 88%
“…28 Inflation-adjusted Medicare compensation per rhinologic procedure decreased significantly with an average total percent decrease of 36.09% for high relative value unit (RVU) procedures. 29 In the other specialties, the average nominal dollar reimbursements have increased or decreased by less than 10%. [25][26][27][28] Though reimbursement trends among subspecialties vary greatly, our findings indicate a disproportionate decline in reimbursement for facial fractures, similar to that of rhinologic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Inflation-adjusted declines in reimbursement have been found not only in neurosurgery, 4 general surgery, 5 orthopedic surgery, 6 reconstructive plastic surgery, 7 ophthalmology, 21,22 and interventional radiology 23 but also in otolaryngology 9 and its subspecialties. 10,11,24 This study found a 20.3% inflation-adjusted decline in reimbursement of laryngeal procedures. Though our study looked at a greater number of procedures within laryngology, this result is largely in line with the recent findings of Quereshy et al who found an inflation-adjusted decline of 19.4% among head and neck surgical oncology CPT codes 12 and Schartz et al who found an inflationadjusted decline of 21.2% among otology procedures.…”
Section: Discussionmentioning
confidence: 68%
“…In approximately the last 2 decades, after adjusting for inflation, reimbursements have declined 25.8% in neurosurgery, 4 24.4% in general surgery, 5 29.0% in orthopedic surgery, 6 14.0% in reconstructive plastic surgery, 7 and 29.1% in emergency medicine. 8 Similar, yet further declining, trends have been seen in the field of otolaryngology with inflation-adjusted reimbursements falling 37.6% for the 20 most performed otolaryngology procedures, 9 21.2% for otology procedures, 10 43.1% for rhinology procedures, 11 and 19.4% for head and neck surgical oncology procedures. 12 The objective of this study is to investigate Medicare reimbursement trends for commonly performed laryngeal procedures.…”
mentioning
confidence: 99%
“…24,25 The paucity of ORL physicians in rural areas may be at least partially attributable to lower patient volumes and the resulting challenges of financially sustainable practice, especially given recent trends of declining reimbursements in otolaryngology and its subspecialties. 15,[26][27][28] In addition to relative value units (RVUs), geographic practice cost indices, which take into account physician work, practice expense, and malpractice insurance, are used in calculation of a geographic adjustment factor (GAF) that determines the amount a physician is reimbursed. 29 Localities like North and South Dakota have a GAF of around 0.88 while San Francisco, California, has a GAF of around 1.2.…”
Section: Discussionmentioning
confidence: 99%